2013
DOI: 10.1016/j.bmc.2013.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Ascaroside activity in Caenorhabditis elegans is highly dependent on chemical structure

Abstract: The nematode Caenorhabditis elegans secretes ascarosides, structurally diverse derivatives of the 3,6-dideoxysugar ascarylose, and uses them in chemical communication. At high population densities, specific ascarosides, which are together known as the dauer pheromone, trigger entry into the stress-resistant dauer larval stage. In order to study the structure-activity relationships for the ascarosides, we synthesized a panel of ascarosides and tested them for dauer-inducing activity. This panel includes a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Ascarosides were synthesized as previously described (34), and (R)-6-hydroxyheptanoic acid and (R)-8-hydroxynonanoic acid were synthesized as described in SI Materials and Methods. CoA-thioesters of ascarosides, fatty acids, and hydroxylated fatty acids (1-9) were synthesized based on a previously described method for making fatty acylCoA thioesters (35) with modifications (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Ascarosides were synthesized as previously described (34), and (R)-6-hydroxyheptanoic acid and (R)-8-hydroxynonanoic acid were synthesized as described in SI Materials and Methods. CoA-thioesters of ascarosides, fatty acids, and hydroxylated fatty acids (1-9) were synthesized based on a previously described method for making fatty acylCoA thioesters (35) with modifications (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Ascarosides were synthesized as described previously (28). Pentanoic, heptanoic, and nonanoic acid were purchased (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…50,51 For example, ascr#10, featuring a saturated 9-carbon side chain, strongly attracts hermaphrodites (Fig. 3), whereas ascr#3, which differs from ascr#10 only in that its side chain includes a double bond, acts as a deterrent (Fig.…”
Section: The Discovery Of Ascaroside-based Signalling In the Model mentioning
confidence: 99%
“…44,46 The indole ascaroside icas#9, featuring a saturated 5-carbon side chain, additionally exhibits dauer inducing activity, 45 whereas ascr#9, lacking the indole carboxy moiety, is not active in this assay. 51 Extensive HPLC-MS analyses of worm exo -metabolome and worm body extract samples have demonstrated that attachment of the tryptophan-derived indole carboxy moiety is tightly controlled. For example, the potent attraction pheromones icas#3 and icas#9 are present in almost identical amounts (Fig.…”
Section: The Discovery Of Ascaroside-based Signalling In the Model mentioning
confidence: 99%